Pemanfaatan Microsoft Excel untuk Aplikasi Data Pelanggan pada Pada Usaha Jasa Pembersihan Dan Perawatan Sepatu, Tas, Dan Topi - Fajar Astuti Hermawati; Aidil Primasetya Armin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Scar Wash is a micro-business engaged in the care and cleaning of bags, hats and shoes located in the Karang Menjangan area of ​​Surabaya. In the process, partners face problems in the process of storing customer data is still done in the manual form. So it isn't easy in knowing information about customers and what transactions have been made by satisfied customers to improve service. Since of these reasons, we offer to create desktop applications by utilizing a Microsoft Excel spreadsheet application that is quite familiar to business owners. The system consists of three main menus, namely the customer data, the service data and the transaction menu. The customer data menu is for storing customer data. The service data menu is for managing service data provided by partners and the rates of each service provided. The transaction menu is used to record every transaction of a customer that includes services and the total cost that the customer must pay. This application has the advantage of being easy to install. After all, it does not require software other than Microsoft Excel, small and fast because it runs directly on the Excel application itself and is easy to use because it has a combo-box facility for selecting customer data and service data